Chemical and Instrumental Analysis of Limestone and Red Clay from Makwanpur District for Cement Production - Dubey, Rupesh Kumar; Bhatta, Bishan Datta (Journal of Nepal Chemical Society, 2023)
Limestone and red clay are widely used in construction as primary raw materials since they are readily available and economically viable. The present work has been carried out primarily to explore the fresh reserves of acceptable raw materials in the Makawanpur district for producing cement. Four limestone and four red clay samples were collected from different locations in the Makwanpur district. The samples were analyzed using chemical (titrimetric and gravimetric) and instrumental (wave dispersive X-ray fluoroscopy, WDXRF) methods. Chemical, as well as instrumental methods, were utilized not only to authenticate the results but also to evaluate the merits of these methods. Loss on ignition (LOI), determined gravimetrically, ranged from 41.98 to 39.03% for limestone samples and from 9.24 to 7.82% for red clay samples.Chemical analysis of limestone samples revealed the presence of 40.72 to 48.53% CaO, 0.97 to 1.96% Fe2O3, 1.83 to 3.64% Al2O3 and 5.69 to 12.84% SiO2. Chemical analysis of red clay revealed the presence of 2.26 to 3.27% CaO, 9.54 to 14.20% Fe2O3, 12.90 to 19.68% Al2O3 and 46.70 to 61.50% SiO2. The WDXRF analysis of limestone revealed the presence of 39.37 to 50.46% CaO, 0.8 to 2.29% Fe2O3, 1.34 to 3.01% Al2O3 and 4.75 to 17.03% SiO2. The WDXRF analysis of red clay revealed the presence of 1.98 to 3.59% CaO, 9.89 to 13.96% Fe2O3, 12.45 to 19.82% Al2O3 and 47.62 to 60.94% SiO2. The analyzed compositions were found to lie within the range allowed by the Nepal Bureau of Standards and Metrology (NBSM) for the manufacture of high-quality cement. The results from the chemical methods were found to be in good agreement with the results from the instrumental method. This research is expected to contribute to the cement industry not only by providing insight into raw material compatibility but also by evaluating the merits of these methods.